Impact of removable partial denture prosthesis on chewing efficiency - Marion Bessadet; Emmanuel Nicolas; Marine Sochat; Martine Hennequin; Jean-Luc Veyrune (University of São Paulo, 2013)
Removable partial denture prostheses are still being used for anatomic, medical and economic reasons. However, the impact on chewing parameters is poorly described. OBJECTIVES: The objective of this study was to estimate the impact of removable partial denture prosthesis on masticatory parameters. MATERIAL AND METHODS: Nineteen removable partial denture prosthesis (RPDP) wearers participated in the study. Among them, 10 subjects were Kennedy Class III partially edentulous and 9 with posterior edentulism (Class I). All presented a complete and full dentate opposing arch. The subjects chewed samples of carrots and peanuts with and without their prosthesis. The granulometry of the expectorated boluses from carrot and peanuts was characterized by median particle size (D50), determined at the natural point of swallowing. Number of chewing cycles (CC), chewing time (CT) and chewing frequency (CF=CC/CT) were video recorded. RESULTS: With RPDP, the mean D50 values for carrot and peanuts were lower [Repeated Model Procedures (RMP), F=15, p<0.001] regardless of the type of Kennedy Class. For each food, mean CC, CT and CF values recorded decreased (RMP, F=18, F=9, and F=20 respectively, p<0.01). With or without RPD, the boluses' granulometry values were above the masticatory normative index (MNI) determined as 4,000 µm. CONCLUSION: RPDP rehabilitation improves the ability to reduce the bolus particle size, but does not reestablish fully the masticatory function. CLINICAL RELEVANCE: This study encourages the clinical improvement of oral rehabilitation procedure.